PERAN ORANG TUA TERHADAP PENINGKATAN PRESTASI BELAJAR PENDIDIKAN AGAMA ISLAM ANAK - Suroto Suroto (Education Enthusiast : Jurnal Pendidikan dan Keguruan, 2022)
The family will have a great influence on the growth and development of children in the future. A family that will provide a discourse on a child's life, both behavior, character, and daily habits. Parents are required to have adequate knowledge and education, so that their children will get the opportunity to learn from their parents, and parental education will have a positive impact on the development of children's learning achievements. From the description above, the author is interested in conducting a scientific study on the role of parents on the achievement of children's Islamic education.